Perbandingan Teknik Akupresur Dengan Kompres Air Jahe Sebagai Teknik Pengurangan Rasa Nyeri Guna Mengatasi Keluhan Sakit Pinggang Pada Ibu Trimester III Kehamilan Di Wilayah Kerja Puskesmas Cibeber - Sri Maryati; Damai Yanti; Karwati Karwati (Health Idea, 2024)
Pain is a very common problem in pregnancy, especially in the third trimester. Pain, defined by the International Society For The Study Of Pain as “an unpleasant sensory and emotional experience arising from actual or potential tissue damage”, causes fear and anxiety that can increase stress and drastic physiological changes during pregnancy. A common problem experienced by pregnant women in the third trimester is lower back pain, with around 70% of women complaining of some form of lower back and back pain at some point during pregnancy, childbirth and postpartum. This is caused by the burden of the stomach and changes in the spine and ligaments. If not treated properly, this pain can reduce the quality of life of pregnant women. Therapies that can be given to mothers with lower back pain are Acupressure and ginger water compresses. The purpose of this study was to determine the comparative effectiveness of acupressure techniques with ginger water compresses as pain reduction techniques in overcoming complaints of back pain in pregnant women in the third trimester in the Cibeber Health Center work area. This study was a quasi-experiment with a post-test only design, statistical tests using one way ANOVA. Samples were taken by accidental sampling, with research subjects being pregnant women in the third trimester who visited PMB "K" and PMB "R" in November - December 2023. The results of the study at PMB in the Cibeber area showed that the average pain scale results in the acupressure group on days 2, 4 and 6 were 4.25; 2.35; 1.50 with a p value of 0.0001; while in the ginger water compress group on days 2, 4 and 6 were 4.15; 3.35; 2.50 with a p value of 0.006. In conclusion, there is a difference in the scale of lower back pain in mothers before and after being given a combination of Acupressure massage and ginger water compress therapy. This therapy is expected to be taught by health workers, especially midwives, to the patient's family so that it can be done independently, provide a strong psychological effect, and support a safe, smooth, and enjoyable delivery process. The output produced in this study is publication in a national journal with ISSN. Keywords: pain reduction; waist of pregnant women trimester III; acupressure; ginger water compress